Psychological Flexibility and Cyberchondria: Moderating Effect of COVID-19 Anxiety - Mehrdad Pourshahbazi; Mahdi Imani; Mahdi reza Sarafraz; Mohammad ali Goodarzi (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2024)
Aim and Background: In addition to inflicting distress and functional impairment, the Cyberchondria phenomenon could cause a heavy burden to healthcare professionals by increasing in number of visitors to hospitals and medical centers. Cyberchondria can be helpful in choosing and designing psychological interventions. Therefore, this study aimed to explore relationships between two components of psychological flexibility (Mindfulness and Cognitive diffusion) to Cyberchondria and the possible moderator effect of COVID-19 Anxiety in this relationship. Methods and Materials: The method used in this study was descriptive and correlational. The statistical population included all students who were studying at Shiraz University in the academic year 2021-2022. Convenience Sampling was used to choose participants. Data gathering was done on the Internet because of social distancing obligations. 262 participants completed study questionnaires. The tools used in this research were the Cyberchondria severity scale (CSS), Freiburg Mindfulness Inventory (FMI), Cognitive Fusion Questionnaire, and Corona Disease Anxiety Scale (CDAS). The structural equation modeling method and Lisrel software were used to explore the relationship between study variables. Findings: The presented model has a good fit. No significant relationship was found between mindfulness and cyberchondria. Cognitive Diffusion also had direct and indirect (through COVID-19 Anxiety) effects on Cyberchondria. Therefore, a significant statistical relationship was confirmed between study variables. Conclusions: In sum, it seems cognitive defusion significantly contributes to cyberchondria symptoms, and COVID-19, as a mediant variable, plays a significant part in individuals' vulnerability against cyberchondria.